Influencing Factors Associated With Mental Health Outcomes Among Dental Medical Staff in Emergency Exposed to Coronavirus Disease 2019: A Multicenter Cross-Sectional Study in China - Chen, Yaopian; Li, Wei (Frontiers in Psychiatry, 2021)
Abstract BACKGROUND: The epidemic infection of coronavirus disease-19(COVID-19) may have a profound impact on dentistry, mainly due to the mode of transmission of the pathogen, which poses a risk to almost all dental operations. So the purpose of this study was to assess the relationship between COVID-19 and psychological distress in dental staff during the COVID-19 pandemic. METHODS: A multi-center cross-sectional study was conducted among 808 front-line dental medical personnel working in an emergency department across the Chinese mainland. A self-designed questionnaire was used to collect the general demographic information of the respondents. And the 7-item Generalized Anxiety Disorder scale (GAD-7), the 9-item Patient Health Questionnaire (PHQ-9), the 10-item perceived stress scale (PSS-10) and the Acute Stress Disorder Scale (ASDS) were used to assess the severity of symptoms of anxiety, depression, perceived stress and post-traumatic stress disorder(PTSD), respectively. RESULTS: The prevalence of depression, anxiety, perceived pressure and PTSD among the front-line dental medical staff was 46.4%, 36.3%, 65.2% and 1.1%, respectively. Male reported experiencing more dissociation and PTSD than female (p<0.05); Working in Wuhan area reported experiencing more anxiety and perceived stress than not working in Wuhan area (p<0.05); Working in the general hospital reported experiencing more dissociation symptom and PTSD than working in a specialized hospital or private hospital (p<0.05); Individuals with a past medical history reported experiencing more anxiety, depression, perceived stress and dissociation symptom than those without (p<0.05); and individuals with lower levels of education showed higher levels of anxiety (p<0.05). The results of binary logistic regression analysis (after controlling for other confounders) suggested that having a past medical history was a risk factor for both anxiety (p=0.002, OR=2.400, 95%CI: 1.383~4.303) and perceived stress (p=0.001, OR=1.080, 95%CI: 0.406~1.634). CONCLUSIONS: There was a high prevalence of mental symptoms among the first-line emergency dental staff. Male, working in the Wuhan area, working in a general hospital, with a past medical history and lower levels of education need particular attention. KEYWORDS: COVID-19, anxiety, depression, stress, dentist, Chinese